Giant Thoracolumbosacral Myelomeningocele: A Case Report - Acharya, Abhijit; Panigrahi, Souvagya; Deo, Rama Chandra; Senapati, Satya Bhusan; Mahapatra, Ashok Kumar (Indian Journal of Neurosurgery, 2024)
Neural tube defects are a broad spectrum of congenital developmental anomalies that include cranial defects and open and closed spinal dysraphism. Myelomeningocele is a common form of spinal dysraphism most commonly seen in the lumbosacral region. Giant myelomeningoceles are rare occurrences. We hereby present the case of a 7-month-old infant with a history of large swelling over the thoracic lumbar region (circumference of 42 cm and diameter of 12.5 cm) that was progressively increasing in size with occasional cerebrospinal fluid (CSF) leakage from the swelling. There was associated progressive increasing size of the head size circumference (51 cm) as well for the past 6 months. There was no movement of both lower limbs since birth without any sensation up to the groin. On evaluation, the infant was found to have gross hydrocephalous. The Evans index was 0.4 with Chiari 2 malformation and a giant thoracolumbosacral myelomeningocele. The patient underwent a low-pressure ventriculoperitoneal (VP) shunt on the right side, followed by the repair of the giant myelomeningocele. The post-op period was uneventful with no CSF leakage or skin necrosis. The infant was discharged on day 5. Giant myelomeningoceles are quite a challenge for neurosurgeons due to the high risk of skin edge necrosis, CSF leaks, meningoencephalitis, etc. Here we managed our case with utmost intraoperative surgical skills and postoperative management due to which our patient was discharged in a satisfactory condition without any complication. This case is supposed to be largest myelomeningocele in the world literature to date.
Keywords: myelomeningocele; neurosurgery; spinal dysraphism; tethered cord